The influence of tax rates, profitability, assets, and foreign ownership on transfer pricing in Indonesia’s mining sector: ethical implications in Islamic economics - Fatahila, Alfiyan; Istiariani, Irma (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2024)
The rapid expansion of multinational enterprises (MNEs) has introduced new challenges in managing cross-border transactions, particularly in transfer pricing –a practice used for pricing goods, services, or intangible assets between related entities within a corporate group. This study aims to examine the influence of tax rates, profitability, company assets, and foreign ownership on transfer pricing decisions among mining companies listed on the Indonesia Stock Exchange. The research adopts a quantitative approach, using multiple linear regression analysis on financial data from 33 companies over five years (2017-2021). Results indicate that tax rates and profitability do not significantly impact transfer pricing behavior, while company assets and foreign ownership exhibit a significant negative effect. These findings suggest that larger companies and those with higher foreign ownership are less likely to engage in transfer pricing. The study contributes to the existing literature by incorporating an Islamic economic perspective, emphasizing ethical principles like justice (al-‘adl) and social responsibility (al-amānah) in business practices. The implications highlight the need for stricter regulations and ethical considerations to combat tax avoidance, ensuring fair wealth distribution in alignment with Islamic values.